Meningkatkan Kesadaran Kritis Siswa melalui Strategi Membaca Kritis Teks Naratif - Rizqiani, Diyah Ayu; Herlina, Sari; Astuti, Missi Tri; Novitri, Safriani (LOSARI DIGITAL, 2025)
The Community Service Program (PKM) aimed to enhance the critical awareness of Madrasah Aliyah students through critical reading strategies using narrative texts. The activity was conducted on February 25, 2025, at MA Diniyah Puteri Pekanbaru and involved 25 tenth-grade students. Students were divided into five small groups and analyzed a narrative text titled